2020
DOI: 10.1021/acs.langmuir.0c02492
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molecular Interactions between Surface-Immobilized Antimicrobial Peptides and Lipopolysaccharides In Situ

Abstract: Lipopolysaccharide (LPS) is a component of the outer membrane of Gram-negative bacteria. Recently, a label-free immobilized antimicrobial peptide (AMP) surface plasmon resonance platform was developed to successfully distinguish LPS from multiple bacterial strains. Among the tested AMPs, SMAP29 exhibited excellent affinity with LPS and has two independent LPS-binding sites located at two termini of the peptide. In this study, sum frequency generation vibrational spectroscopy was applied to investigate molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Sum frequency generation (SFG) vibrational spectroscopy has been demonstrated to be a suitable tool to understand the change of molecular structures of surfaces and interfaces. SFG enables precisely measuring the molecular structure/behavior of surfaces/interfaces by its surface/interface-sensitive nature. SFG has been extensively applied to study the surface and interfacial molecular structures of polymers, including various polymer adhesives. , In this study, the atmospheric moisture effect on the surfaces of isocyanate-based primers was probed by SFG, and the molecular behaviors of such surfaces were correlated to the macroscopic properties to investigate the relationship. Different conditions in the experiments were set up in a variation of humidity levels and exposure time to understand the influences of their effects on the primer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy has been demonstrated to be a suitable tool to understand the change of molecular structures of surfaces and interfaces. SFG enables precisely measuring the molecular structure/behavior of surfaces/interfaces by its surface/interface-sensitive nature. SFG has been extensively applied to study the surface and interfacial molecular structures of polymers, including various polymer adhesives. , In this study, the atmospheric moisture effect on the surfaces of isocyanate-based primers was probed by SFG, and the molecular behaviors of such surfaces were correlated to the macroscopic properties to investigate the relationship. Different conditions in the experiments were set up in a variation of humidity levels and exposure time to understand the influences of their effects on the primer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…SFG vibrational spectroscopy (or SFG in short) is a second-order nonlinear optical technique which is submonolayer surface sensitive because of its special selection rule: under the electric dipole approximation, SFG signal can only be generated from a medium with no inversion symmetry. SFG probes the macroscopic second-order nonlinear susceptibility χ (2) of a material, while χ (2) is nonzero only for a sample with no inversion symmetry. , Most bulk media are centrosymmetric, thus do not have SFG signal, while surfaces and interfaces lack inversion symmetry and can generate SFG signals. For a charged interface like silica–water interface, it is believed and shown that there are bulk (3) contributions from the electric double layer/diffuse layer near the silica–water interface.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Here we studied nonionic surfactants and water at the silica–surfactant solution interface. SFG is a surface-specific second-order nonlinear optical spectroscopy probing second-order nonlinear susceptibility χ (2) of a medium, which has been developed into a powerful tool to investigate surfaces and interfaces. We have applied SFG to study a variety of complex surfaces and interfaces including biological molecules, polymers, as well as surfactants. , The silica–water interfaces have been extensively studied by SFG in various aspects. Silanol groups on a silica surface can be deprotonated in an aqueous solution under neutral pH (SiOH ⇄ SiO – + H + ), which results in a negatively charged silica surface in contact with water. , Different surface structures of silica can form different types of hydrogen bonding with water at the buried silica–water interface, making water molecules ordered at the immediate silica–water interface (the nearest water layer on silica), which contribute to SFG signals. …”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical technique with intrinsic interface sensitivity. SFG has been extensively employed to study molecular structures of solid/liquid interfaces. We have demonstrated that the valuable molecular information for polymer/solution interfaces obtained by SFG can contribute to the elucidation of interfacial behaviors of polymer, water, and biological molecules. , To gain fundamental understandings of the interfacial behaviors in CFRP, SFG was applied to characterize the molecular structures of carbon fiber/sizing solution and plastic/sizing solution interfaces in this study.…”
Section: Introductionmentioning
confidence: 99%